2002
DOI: 10.1073/pnas.052023499
|View full text |Cite
|
Sign up to set email alerts
|

Cortex mapping reveals regionally specific patterns of genetic and disease-specific gray-matter deficits in twins discordant for schizophrenia

Abstract: The symptoms of schizophrenia imply disruption to brain systems supporting higher-order cognitive activity, but whether these systems are impacted differentially against a background of diffuse cortical gray-matter deficit remains ambiguous. Some unaffected first-degree relatives of schizophrenics also manifest cortical gray-matter deficits, but it is unclear whether these changes are isomorphic with those in patients, and the answer is critical to understanding the neurobiological conditions necessary for dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
190
0
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 283 publications
(211 citation statements)
references
References 51 publications
(71 reference statements)
14
190
0
6
Order By: Relevance
“…People at high risk of psychosis show qualitatively similar volumetric abnormalities to patients with schizophrenia. Cortical brain abnormalities have been found in genetically defined high-risk populations such as first-degree relatives and co-twins of patients with schizophrenia, as well in people with ARMS [13,[68][69][70][71][72][73][74][75][76][77][78][79][80]. Previous longitudinal MRI studies in this group found that the subset of patients who developed psychosis showed a longitudinal reduction in GM in the orbito-frontal, temporal lobe, parietal lobe and cerebellum [79,81,82].…”
Section: Effects Of Antipsychotic Medication On Structural Neuroimagimentioning
confidence: 82%
“…People at high risk of psychosis show qualitatively similar volumetric abnormalities to patients with schizophrenia. Cortical brain abnormalities have been found in genetically defined high-risk populations such as first-degree relatives and co-twins of patients with schizophrenia, as well in people with ARMS [13,[68][69][70][71][72][73][74][75][76][77][78][79][80]. Previous longitudinal MRI studies in this group found that the subset of patients who developed psychosis showed a longitudinal reduction in GM in the orbito-frontal, temporal lobe, parietal lobe and cerebellum [79,81,82].…”
Section: Effects Of Antipsychotic Medication On Structural Neuroimagimentioning
confidence: 82%
“…Nevertheless, studies indicate that cortical surface parameters are linked to neurodevelopmental processes that undergo only partial reshaping across the lifespan (Wienberger and McClure, 2002;Mangin et al, 2010). Surface parameters can be viewed as promising endophenotypes (Cannon et al, 2002;Goghari et al, 2007;Goldman et al, 2009;Qiu et al, 2010). Methods for characterizing cortical surface morphology, for example, by folding patterns, continue to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Disease-specific deficits correlated with symptom severity and working and episodic memory impairment, but not with illness duration or treatment. (b) Significance map of genetic liability-related deficits: Gray matter deficits correlated with genetic proximity to a patient in polar and superior prefrontal cortex [Cannon et al 2002]. (c) Callosal surface averages mapped in groups defined by biological risk for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the topography of genetically encoded deficits in cortical gray matter in schizophrenia, we created the first three-dimensional cortical surface maps of intrapair differences in MZ and DZ twins discordant for SZ (10 discordant pairs of each zygosity), along with 10 pairs of demographically matched control twins of each zygosity [Cannon et al, 2002] (Fig. 3).…”
Section: Heritability Of Brain Structure In Twins Discordant For Schimentioning
confidence: 99%